Conjugative transfer frequencies of mef(A)‐containing Tn1207.3 to macrolide‐susceptible Streptococcus pyogenes belonging to different emm types. (1st April 2014) - Hadjirin, N.F.; Harrison, E.M.; Holmes, M.A.; Paterson, G.K.
Abstract: The aim of this study was to examine the gene transfer potential of mef (A)‐containing Tn 120.3 to macrolide‐susceptible Streptococcus pyogenes belonging to different emm types. Using the filter mating technique, Tn 1207.3 was transferred by conjugation to 23 macrolide‐susceptible recipients representing 11 emm types. PCR analysis confirmed the presence of the mef (A) gene and the comEC junction regions of the Tn 1207.3 insertion in resultant transconjugants. Significant variation was found in the transfer frequency of Tn 1207 . 3 to different Strep . pyogenes strains, and this phenomenon may contribute to the differences in mef (A) frequency observed among clinical isolates. Significance and Impact of the Study: The spread of antimicrobial resistance among pathogenic bacteria is an important problem, but the mechanisms of horizontal transfer between strains and species are often poorly understood. For instance, little is known on how macrolide resistance spreads between strains of the human pathogen Strep. pyogenes and why certain strains more commonly display resistance than others. Here, we show that Strep . pyogenes strains vary greatly in their ability to acquire a transposon encoding macrolide resistance by horizontal gene transfer in vitro . These data provide a novel insight into the transfer of antibiotic resistance between bacterial strains and offer an explanation for the differences in the frequency of resistance determinates and resistance seen among clinical isolates.